2018
DOI: 10.20546/ijcmas.2018.705.198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Reproductive Disorders in Niali and Kantapara Block of Cuttack District, Odisha, India

Abstract: A survey was conducted to study the incidence of infertility in crossbred cows and distribution of repeat breeding crossbred animals in Niali and Kantapara block of Cuttack district, Odisha, India which revealed that, the incidence of reproductive problems were 45.18 per cent in cross bred cows and 25.47 per cent in heifers. Out of the total reproductive disorders, 36.89, 51.94 and 11.17 per cent of cases were recorded as postpartum anoestrus, repeat breeding and miscellaneous disorders, respectively in crossb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Kutty and Ramachandran, (2003) also observed a high prevalence of RB (35 %) among crossbred cattle of Kerala. However, Harichandan et al (2018) reported the highest (51.94%) incidence of RB in dairy cows, in India. The incidence of RB varied with the season, number of calvings, body condition score, average days in milk etc.…”
Section: Abstract: Cytological Endometritis Occurrence Repeat Breedingmentioning
confidence: 94%
“…Kutty and Ramachandran, (2003) also observed a high prevalence of RB (35 %) among crossbred cattle of Kerala. However, Harichandan et al (2018) reported the highest (51.94%) incidence of RB in dairy cows, in India. The incidence of RB varied with the season, number of calvings, body condition score, average days in milk etc.…”
Section: Abstract: Cytological Endometritis Occurrence Repeat Breedingmentioning
confidence: 94%
“…Repeat breeding (kawin berulang) pada sapi perah merupakan salah satu gangguan reproduksi yang menyebabkan kerugian ekonomi cukup besar bagi peternak karena jumlah inseminasi yang lebih banyak, jarak beranak yang panjang, dan penurunan produksi. Sapi yang mengalami kawin berulang (repeat breeding) adalah sapi betina yang mempunyai siklus dan periode estrus normal, sudah dikawinkan tiga kali atau lebih dengan pejantan fertil atau diinseminasi buatan dengan semen pejantan fertil tetapi tetap belum bunting (Robert, 1986) Kejadian kawin berulang pada sapi persilangan sekitar 36% (Azeez et al, 2017), 25,96% (Arun et al, 2020), pada sapi perah di Daerah Istimewa Yogyakarta 29,4 % (Prihatno et al, 2013), sapi perah di India tertinggi 51,94% (Harichandan et al, 2018), dan 23,60% (Aruna et al, 2021). Penyebab dasar kawin berulang adalah kegagalan fertilisasi dan kematian embrio dini.…”
Section: Pendahuluan Latar Belakangunclassified